2016
DOI: 10.9799/ksfan.2016.29.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and Quality Evaluation of Beverage with prepared with Roasted Seoritae

Abstract: This study was performed to develop and evaluate beverage prepared with optimally roasted seoritae to maximize the isoflavone content and antioxidant activities of the beverage. Isoflavone content was maximized at the roasting temperature of 110℃ for 20 min. Both DPPH radical scavenging activity and ABTS radical scavenging activity along with total polyphenol content were highest when seoritae was roasted at 110℃ for 20 min. Western blotting was used to determine the level of nuclear factor of activated T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These results correlate with the increased anti-oxidative effect of sword bean under light roasting condition heat-treated for about 442 s at 163°C, considering the large seed size of sword bean compared to that of small black bean and mung bean. These results are consistent with studies showing that antioxidant activity is improved by increase of physiologically active substances due to various chemical changes resulting from heat treatment of food [ 3 , 17 , 18 , 50 ]. Therefore, it is possible to increase antioxidant activity by applying the roasting process to sword bean and to remove the off-flavor of raw sword bean.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results correlate with the increased anti-oxidative effect of sword bean under light roasting condition heat-treated for about 442 s at 163°C, considering the large seed size of sword bean compared to that of small black bean and mung bean. These results are consistent with studies showing that antioxidant activity is improved by increase of physiologically active substances due to various chemical changes resulting from heat treatment of food [ 3 , 17 , 18 , 50 ]. Therefore, it is possible to increase antioxidant activity by applying the roasting process to sword bean and to remove the off-flavor of raw sword bean.…”
Section: Resultssupporting
confidence: 92%
“…Jeong et al . [ 18 ] reported that roasting seoritae (black bean) at 110°C for 20 min showed the highest content of isoflavone and antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation